2022
DOI: 10.1038/s41529-022-00304-7
|View full text |Cite
|
Sign up to set email alerts
|

Steel rust layers immersed in the South China Sea with a highly corrosive Desulfovibrio strain

Abstract: Although it is well known that microbes play a significant role in marine corrosion, few studies have systematically studied the relationship between microorganisms and corrosion products under long-term immersion. In this study, the corrosion characteristics of the rust layer formed on carbon steel immersed in the South China Sea for 5.5 years were investigated using various surface analysis and microbial community analysis techniques. Magnetite (Fe3O4), iron sulfide, and green rust were identified in the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Recent advances in genomics and metabolic pathways have led to new insights into the ecophysiology and distribution of SRB in the marine environment. For instance, studies have demonstrated that SRB is the primary microorganism involved in the long-term seawater immersion process [ 17 ]. Prominent SRB species such as Desulfovibrio and Desulfobacter have been detected in the inner layer of carbon steel, with a significantly higher abundance index than other bacterial species [ 18 ].…”
Section: Microorganisms Involved In Marine Micmentioning
confidence: 99%
“…Recent advances in genomics and metabolic pathways have led to new insights into the ecophysiology and distribution of SRB in the marine environment. For instance, studies have demonstrated that SRB is the primary microorganism involved in the long-term seawater immersion process [ 17 ]. Prominent SRB species such as Desulfovibrio and Desulfobacter have been detected in the inner layer of carbon steel, with a significantly higher abundance index than other bacterial species [ 18 ].…”
Section: Microorganisms Involved In Marine Micmentioning
confidence: 99%
“…[7][8][9] Furthermore, oxidants such as sulfate, nitrate, and carbon nutrients readily available in oilfield produced water boost microbial metabolism and cell proliferation. [9,10] According to Dong et al [11] microorganisms synergize with the rust layers formed on carbon steel in the marine environment to exacerbate MIC. Studying the contribution of each component in the deposit will be helpful in a better understanding of the UD-MIC mechanism.…”
Section: Introductionmentioning
confidence: 99%